PENGARUH DISIPLIN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MODERATING PADA PT. PLN UNIT PELAKSANA PELAYANAN PELANGGAN (UP3) SITUBONDO - Samudra, Arung; Praja, Yudha; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The PT. PLN Situbondo Customer Service Implementation Unit (UP3) is oriented towards fulfilling environmentally friendly energy policies, distributing electricity for the public interest, general tasks of providing services to customers, carrying out maintenance and repairs to the electricity network, ensuring stable electricity supply for customers, providing efficient customer service , including complaint handling, new installations, electricity replacement, and temporary outages. The aim of this research is to analyze the influence of Work Discipline, Competency and Motivation on employee performance at the Customer Service Implementation Unit (UP3) PT PLN Situbondo. The population in this study was employees of PT. PLN Situbondo Customer Service Implementation Unit (UP3). This research was conducted using a quantitative approach and the sampling technique was determined by quota sampling. The data analysis and hypothesis testing in this research used the Structural Equation Model– Partial Least Square (PLS-SEM). The results of hypothesis testing using the Smart PLS 3.0 application show that Work Discipline has a significant effect on Performance, Competence has a significant effect on Performance. The results of hypothesis testing which is moderated by the Motivation variable show that the Work Discipline variable has a negative effect on Performance but is not significant, the Competency variable which is moderated by Motivation shows a positive effect on Performance but is not significant.